Comparative Studies of the Effects of Egg Yolk, Oats, Apple, and Wheat Bran on Serum Lipid Profile of Wistar Rats. (12th December 2012) - Omole, J. O.; Ighodaro, O. M.
Abstract : Excess consumption of egg especially its yolk has been implicated in hyperlipidaemia (high level of cholesterol and triglyceride in the blood). Conversely, soluble dietary fibers, probably due to their ability to bind free lipid molecules, appear to play an important role in protecting against hyperlipidaemia. This study sought to evaluate the comparative effects of selected sources of fibers: apple, oats, and wheat bran, on serum lipid profile in physiologically normal Wistar rats. Twenty rats were used for the study and were randomized into four groups, with each containing five animals (n = 5 ). A group which serves as control was fed with egg yolk while the other three groups were fed with apple, oats, and wheat bran, respectively. After two weeks of feeding, the animals were fasted overnight and blood samples from the retro-orbital sinus of the eye were collected for analyses of lipid profile. The results obtained showed that the group fed with oats had the lowest level of total cholesterol (82.9 ± 1.8 mg), low density lipoprotein (LDL) cholesterol (49.3 ± 1.4 mg), and triglycerides (TG) (75.1 ± 1.7 mg), as well as the highest level of HDL cholesterol (33.9 ± 0.9 mg). On the contrary, the group fed with egg yolk showed the highest level of total cholesterol (117.1 ± 4.4 mg), LDL cholesterol (96.4 ± 1.5 mg), and triacylglyceride (109 ± 2.6 mg), as well as the lowest level of HDL cholesterol (18.5 ± 0.9 mg). There was no significant difference (P < 0.05 ) between oats and apple in their effects on blood lipid profile of Wistar rats. Wheat bran, being an insoluble dietary fibre, had less significant (P < 0.05 ) effect on the blood lipid profile when compared to oats and apple. Findings from this study may assist physicians and dieticians in recommending appropriate diet for individuals desiring to normalize their blood lipids levels.